Potensi Tradisi Sapat Taun dalam Pembelajaran Sejarah Berbasis Kearifan Lokal: Kajian Literatur - Loppias Lai Simon; Siswandi Siswandi; Pitalis Mawardi Baging (Jurnal Artefak, 2026)
This study aims to examine the potential of the Sapat Taun tradition as a source of history education based on local wisdom. This study employs a descriptive-qualitative literature review approach by analyzing various national and international scholarly sources relevant to local traditions, history education, and cultural heritage education. The results of the study indicate that the Sapat Taun tradition contains historical, social, cultural, spiritual, and ecological values that can be utilized in contextual and meaningful history education. This tradition embodies the values of mutual cooperation, respect for ancestors, gratitude, and care for the environment—values that are relevant to strengthening students’ character and cultural identity. Integrating the Sapat Taun tradition into history education has the potential to strengthen historical awareness, appreciation for local culture, and students’ connection to their social environment. Thus, the Sapat Taun tradition deserves to be positioned as a source of history learning based on local wisdom that supports more relevant, reflective learning oriented toward the preservation of regional cultural heritage.